2022
DOI: 10.1088/1755-1315/1024/1/012025
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Gelatin and Citric Acid Concentration on Chemical and Organoleptic Properties of Jelly Citrus

Abstract: Jelly candy is one type of soft candy that is demand by all age groups, especially children. This study was aimed to determine the optimal combination of gelatin and citric acid concentration in producing jelly candy from Tangerine citrus (Citrus reticulata var. Siam Banjar) based on the organoleptic properties. The study used a factorial completely randomized design, using gelatin and citric acid concentration as a factor, each consisted of 3 levels treatments, those are: 6% w/v, 8% w/v, 10% w/v for gelatin c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 17 publications
0
1
0
Order By: Relevance
“…This is in line with research (Iskandar, Ningtyias, & Rohmawati, 2019) in the study of adding Moringa leaf powder to ice cream which showed that the addition of Moringa leaf flour to ice cream caused a change in taste. The more addition of Moringa leaf powder, the more taste distinctive Moringa leavesIn research (Lesmayati, Qomariah, Awanis, & Anggreany, 2022). Orange jelly candy shows the taste of orange jelly candy is influenced by the interaction between sucrose, which gives a sweet taste, and the concentration of citric acid which gives sour taste.…”
Section: Aspects Of Tastementioning
confidence: 99%
“…This is in line with research (Iskandar, Ningtyias, & Rohmawati, 2019) in the study of adding Moringa leaf powder to ice cream which showed that the addition of Moringa leaf flour to ice cream caused a change in taste. The more addition of Moringa leaf powder, the more taste distinctive Moringa leavesIn research (Lesmayati, Qomariah, Awanis, & Anggreany, 2022). Orange jelly candy shows the taste of orange jelly candy is influenced by the interaction between sucrose, which gives a sweet taste, and the concentration of citric acid which gives sour taste.…”
Section: Aspects Of Tastementioning
confidence: 99%